Minority, cause of general differences in the application of criminal treatment - Popoviciu, Laura-Roxana (International Journal of Legal and Social Order, 2023)
This article deals with the particular aspects regarding the criminal treatment that applies to a special category of offenders, namely the category of juvenile offenders. Beyond any attempt by society to involve in educating man from the earliest age, his antisocial manifestation is a reality of contemporary society and society in general, since ancient times. An unexpected violence on the part of a child, seemingly harmless, always produces a surprise effect, often associated with some form of misunderstanding on the part of the child of what he has manifested. To the child, the adult associates an image of purity and innocence. Unfortunately, at the level of objective reality, things are not always like that, so an important segment among children, minors, is drawn into a complex and extremely harmful phenomenon for society, the criminal phenomenon. Although part of the general criminal phenomenon, the criminality of minors raises some special problems within the penal legislation, completely different from those concerning the criminality of adults. This aspect is determined by the special quality of the criminal, that of a child, a minor. In this article, we will address the particular aspect of the quality of a minor in order to observe that minors benefit from a distinct criminal treatment compared to adults, when they intentionally or accidentally enter what is called the field of criminal law.